An Analysis of Ambiguity and Conceptual Metaphor Study in The American Eagle Campaign Featuring Sydney Sweeney - Utami, Desy Kharisma Putri; Laila, Malikatul; Mujazin, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: Ambiguity is a phenomenon that is inevitable in the process of constructing meaning, while metaphors are attempts to comprehend and perceive something through connecting it to something else. This research aims to explore the ambiguity and conceptual metaphor in the American Eagle campaign featuring Sydney Sweeney. Methodology: The method applied in this study is qualitative research with textual analysis approach toward campaign narration including slogans, campaign titles, advertising dialogue, video narratives, and product descriptions. Results: The findings show that in the American Eagle campaign featuring Sydney Sweeney contain lexical and structural ambiguity in the form of phonetic similarity, semantic broadening, and lack of clarity in syntaxis. Applications/Originality/Value: This research also found that there is a metaphor a concept existed in in the American Eagle campaign featuring Sydney Sweeney.